Institutional and population based analyses on misdiagnosis of appendicitis in Khulna, Bangladesh (Mediscope, 2017)
The aim of the present study was to identify factors associated with misdiagnosis of appendicitis to propose solutions to decrease the misdiagnosis rate of appendicitis. The study conducted an institutional and a population based analyses on misdiagnosis of appendicitis conducted in Khulna district, Bangladesh. The study dealt with 2 groups of patients. Group 1 consisted of the patients treated in Gazi Medical College Hospital (GMCH), Khulna either in out-patient department (OPD) within the last 3 years (from 2014 to 2016), treating doctors suggested appendicectomy and in indoor-patient department (IPD) within the last 5 years (from 2012 to 2016), the diagnosis was done either during operation or admitted as postoperative complications. Patients for Group 2 were selected purposively from the patients who were from different villages of Rupsha and Fakirhat Upazila or from Khulna city previously underwent appendicectomy within the last 5 years (from 2012 to 2016) in different hospitals other than GMCH, Khulna and previous symptoms were still existed. The study revealed that the majority of the patients were female (OPD 81.5%, IPD 68.8% in Group 1 and 83.2% in Group 2). The misdiagnosis rate of appendicitis for the patients attended GMCH OPD and GMCH IPD was 23.0% and 8.9%, respectfully. The overall misdiagnosis rate of appendicitis for the patients attended GMCH was 14.0%. In case of the patients attended GMCH OPD, most of them had UTI and chronic cystitis (45.5%). In case of the patients attended GMCH IPD, most of them had non-inflamed appendix (84.4%). The misdiagnosis rate of appendicitis for the patients in Group 2 was 23.2%. Some factors were identified and bearing in mind the factors, all the concerned should be more careful and conscious while making the diagnosis of appendicitis to avoid misdiagnosis and patients’ suffering.Mediscope Vol. 4, No. 2: Jul 2017, Page 29-34